Volleyball Smash Learning Model for Middle School Students - Weni Wiliya Budiarti; Achmad Sofyan Hanif; Samsudin Samsudin (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This research was conducted to produce a volleyball smash learning model and test its effectiveness for junior high school children. The development method adopts the development steps of Borg and Gall. Small group trials involve 15 athletes and 60 for large group trials. The development of the model begins with small trials, large trials and effectiveness tests. The effectiveness test used pre-post test with the instrument of the volleyball smash skills of junior high school students. The exercise model that was applied was tested for the significance of the difference and it was obtained that the t-test = 31,614, db = 32 and p-value = 0.00 <0.05, meaning that there were significant differences in the ability of students before and after they were given the volleyball smash learning model. It was concluded that existing moddel could be developed and applied in volleyball smash learning and effectively improved volleyball smash learning outcomes for junior high school students.